Data reduction activities at European XFEL: early results - Sobolev, Egor; Schmidt, Philipp; Malka, Janusz; Hammer, David; Boukhelef, Djelloul; Möller, Johannes; Ahmed, Karim; Bean, Richard; Bermúdez Macías, Ivette Jazmín; Bielecki, Johan; Bösenberg, Ulrike; Carinan, Cammille; et al. (Frontiers in Physics, 2024)
The European XFEL is a megahertz repetition-rate facility producing extremely bright and coherent pulses of a few tens of femtoseconds duration. The amount of data generated in the context of user experiments can exceed hundreds of gigabits per second, resulting in tens of petabytes stored every year. These rates and volumes pose significant challenges both for facilities and users thereof. In fact, if unaddressed, extraction and interpretation of scientific content will be hindered, and investment and operational costs will quickly become unsustainable.In this article, we outline challenges and solutions in data reduction.